Three-Dimensional Seepage Characteristics of Yanshan Concrete Slab Dam under Slab Failure and Temporary Flood Conditions - YUE Xiao; CHEN Dewen; HUANG Xinyi; GAN Lei; SHEN Zhenzhong (Renmin Zhujiang)
Concrete slabs and water stop joints are the main seepage control structures of the slab rockfill dams. Slab cracking or water stop failure will significantly affect the distribution of seepage fields in the local area of the cracks or the failure site, which will threaten the normal service performance of the dam. To investigate the seepage safety problems caused by local slab cracking and failure of water stop structures, different positions of slab cracking and water stop failure were designed, and a three-dimensional seepage finite element analysis model of the concrete slab dam of Yanshan pumping and storage power station was established. The evolution law of seepage potential distribution, seepage gradient, and seepage flow rate was studied. The effects of slab cracking and water stop failure were explored, and the sensitivity of the cushion material's permeability coefficient under temporary flood conditions was analyzed. The results show that the seepage flow rate through the slab increases as the water stop structure fails, and the cracking position decreases. Under temporary flood conditions, the maximum average seepage gradient of the cushion decreases with the increase in permeability coefficient. When the permeability coefficient of the cushion increases from 1.0 × 10-5 m/s to 5.0 × 10-5 m/s, the maximum average seepage gradient of the cushion decreases by 1.94. It is suggested that the permeability coefficient of the cushion should be greater than 5.0 × 10-5 m/s, which can improve the stability and safety of cushion seepage under temporary flood conditions. The research results can provide a theoretical basis for the design and construction of a slab rockfill dam anti-seepage system of similar pumping and storage power stations.